Analisis Psikometri Instrumen Psychological Well-Being pada Dokter: Adaptasi Skala Pengukuran - Egan, Hilda; Hapsari, Iriani Indri; Wahyuni, Lussy Dwiutami; Gumelar , Gumgum (Journal of Research and Measurement in Psychology: JPPP, 2025)
This study involved 70 doctors in Indonesia with diverse demographic characteristics, consisting of 54.2% males and 45.8% females, with ages ranging from 25 to 60 years. Based on Rasch analysis using the jMetrik software version 4.1.1, the psychological well-being measurement instrument for doctors in Indonesia showed excellent reliability, with an item reliability value of 0.95 and person reliability of 0.86. These results indicate that the measurement tool used is valid and reliable for this study. The instrument also demonstrated excellent strata separation with a value of 6.77, as well as a range of item difficulty levels, from the easiest to the most difficult. Item number 18 was considered the easiest, while item number 8 was the most difficult. However, item number 26 was found to be unsuitable for the participants and was therefore excluded from the analysis. Overall, the quality of this instrument is rated as excellent, with only two items in the harmony dimension to be used in future research. Keywords: psychological well-being, medical doctor, adaptation, validation, psychometry properties